Redatuming to Improve Hard Rock Seismic Data - Ung, Kai Fu Kevin (Curtin University, 2017)
Land seismic data is generally distorted by complex wave propagation through the regolith. This distortion greatly impedes the standard processing and imaging methods. I try to address this by transforming the data into a dataset that would correspond to a virtual acquisition surface below the regolith. I describe, modify and test several such redatuming methods on synthetic data. These tests then inform my application of the methods to field data, which show promising results.